ASSESSING THE IMPLEMENTATION AND OUTCOMES OF SIERRA LEONE’S RADICAL INCLUSION POLICY FOR MARGINALIZED LEARNERS - Marah, Thomas Sheku (Jurnal Pendidikan Ilmu Sosial, 2025)
The Sierra Leone National Policy on radical inclusion in Schools was created to deal with inequalities in the education of pregnant girls, teenagers, children with disabilities, and rural and lower-income students. This paper evaluates the implementation of the policy, the disabilities that hinder its effectiveness, and the impacts on marginalized learners by conducting a qualitative desk-based review of government reports, peer-reviewed articles, international agencies’ reports, and recent research on inclusive education in Sierra Leone. Results indicate that radical inclusion has helped to reinforce the legislative framework, enhance advocacy, increase opportunities for pregnant learners to return to school, and enrich provisions for learners with special needs. Nevertheless, there is still a lack of effective implementation, including incompetence in inclusive and special needs instruction among teachers, inadequate facilities, ineffective data systems, cultural stigmatization, and economic constraints affecting rural and disadvantaged populations. Ongoingchallenges within the Education Management Information System (EMIS) undermine effective monitoring of inclusion indicators. Given that the study relies more on sources of secondary data, the findings present patterns of implementation and reported results instead of empirical evidence from schools or learners. Despite its limitations, the policy has clear potential when supported by strong school leadership, meaningful community involvement, and also sustained long-term investment. The findings of this study demonstrate that the radical inclusion policy marks a very important step toward achieving equality in the educational system of Sierra Leone, but fulfilling these promises requires deliberate and targeted actions to remove systemic barriers, empower teachers, and strengthen data-driven accountability systems.